Induction of Labor in Preeclamptic Women in India: A Randomized Trial Comparing Foley Catheter With Oral Misoprostol [8I]. (May 2016) - Mundle, Shuchita; Bracken, Hillary; Faragher, Brian; Easterling, Thomas; Winikoff, Beverly; Weeks, Andrew
Abstract : INTRODUCTION: Between 40, 000 and 80, 000 women die annually from pre-eclampsia/eclampsia. Prompt delivery, preferably by vaginal route, is vital for good maternal and neonatal outcomes. Two low cost interventions—oral misoprostol tablets and transcervical Foley catheterization—are already used in low resource settings, but their relative risks and benefits are not known. METHODS: 602 women with a live fetus requiring delivery for pre-eclampsia or uncontrolled hypertension were randomly assigned to cervical ripening with oral misoprostol 25 micrograms every 2 hours (maximum of 12 doses) or a transcervical Foley catheter (size 18 F with 30 mL balloon) which remained until active labor started, the Foley catheter fell out, or 12 hours elapsed. Induction continued with artificial membrane rupture and oxytocin. RESULTS: More women in the misoprostol arm had a vaginal birth within 24 hours (57.0% vs 47.0%; P =.014). Women induced with misoprostol were more likely to have a vaginal birth (59.3% vs 49.7%; P =.017) and with a shorter time to delivery (771 minutes vs 861 minutes; P =.013). Oxytocin requirements were higher in the Foley arm. Rates of uterine hyperstimulation were very low in both groups (0.7% vs 0.3%; P =.566) and no differences were seen in neonatal morbidity. More women in the misoprostol group would use the same method in the future should they require another induction (82.8% vs 72.0%; P =.006). CONCLUSION: Oral misoprostol 25 micrograms was more effective and more acceptable to women than a transcervical Foley catheter for induction of labor in women requiring delivery because of pre-eclampsia or uncontrolled hypertension.